Analysis of Nurseâs Occupational Health in Managing Patients in Benyamin Guluh Hospital Kolaka Regency - Tukatman, Tukatman; Sulistiawati, Sulistiawati; Purwaningsih, Purwaningsih; Nursalam, Nursalam (Jurnal NERS, 2015)
Introduction: Occupational health and safety are a system designed to ensure a good safety and health in the workplace. Nurses have a higher risk of accidents and occupational diseases due to managing patients The goal of analyze the relationship or the influence of predisposing, enabling and reinforcing factors, and the concept of core and care in nursesâ safety and occupational health issue nurs in managing patient. Methods: Type of study is explanatory research using cross sectional design. Proportional random was chosen by consecutive sampling technique amounted to 100 respondents based on criteria. The variables measured were predisposing factors (knowledge, attitudes, beliefs and values), reinforcing factor (officers who became a role model), enabling factors (facilities, rules/regulation), core-care (interpersonal, concern), as well as safety and occupational health. Data were analyzed using Partial Least Square (PLS). Result and Analysis: Predisposing factors affecting safety and occupational health, value by t-count of 2.82 > t-table of 1.96. Reinforcing factors do not significantly affect occupational health and safety by t-count of 1.098 < t-table of 1.96. Enabling factors affecting occupational health and safety by t-count of 2.39 > t-table of 1. Factors of core and care factors affecting nursesâ safety and occupational health in managing patients in Benyamin Guluh Hospital, Kolaka Regency have t-count of 1.963 > t-table of 1.96. Discussion and Conclusion: Development of behavioral and nursing theories to nursesâ occupational health and safety showed R-square value of 39.5%. The new model structure are: predisposing factors (knowledge, attitudes, beliefs and values), enabling factors (facilities, rules / regulation), core (interpersonal relationships) and care (concern).Keywords: occupational health, behavior, nursing